2019
DOI: 10.1002/lpor.201900204
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Tunable Surface Lattice Induced Transparency in a Plasmonic Metasurface

Abstract: Collective coherent scattering at the surface of a plasmonic nanoparticle array is shown to induce tunable transparency windows at the localized plasmon band. Broadband phase measurements show that the enhanced transmission is accompanied by a large anomalous dispersion, which leads to a group delay as large as within only 40 nm thick sample. This effect occurs over a wide tunable spectral range of , and appears for two distinct counter‐propagating surface waves. The experimental observations are in good agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…These EIT‐like features arise due to the interaction of the individual plasmonic particles with a lattice mode, as further described in ref. [ 41 ] . For comparison, we also simulated the phase (Figure 4c) and transmission (Figure 4d) of the measured metasurface with FDTD solver.…”
Section: Resultsmentioning
confidence: 99%
“…These EIT‐like features arise due to the interaction of the individual plasmonic particles with a lattice mode, as further described in ref. [ 41 ] . For comparison, we also simulated the phase (Figure 4c) and transmission (Figure 4d) of the measured metasurface with FDTD solver.…”
Section: Resultsmentioning
confidence: 99%
“…[286][287][288][289][290][291][292][293] Owing to the formation of a collective optical response and its coupling to the in-plane diffraction orders of the array, substantially high-Q lineshapes associated with the SLRs can be excited. [294] While theoretical studies confirmed the excitation of SLR lineshapes with Q-factors on the order of 10 3 , in a recent work, the possibility of achieving experimentally sharp SLRs (up to 2340) was verified. [293] Such pronouncedly high-Q metasurfaces are capable of developing diverse and efficient plasmonic devices including ultrasensitive metasensors.…”
Section: Surface Lattice Resonance (Slr) Metasensorsmentioning
confidence: 96%
“…Figure 7 comprises SEM images of various types of SLR-resonant metasurfaces from recent studies. [293,[294][295][296][297][298] From the biosensing perspective, the promise of SLR modes in periodically decorated resonators for sensing applications has initially been demonstrated in plasmonic platforms. [299][300][301] As one of the leading research teams, Rivas' group utilized SLR modes to scale the FOM of plasmonic sensors.…”
Section: Surface Lattice Resonance (Slr) Metasensorsmentioning
confidence: 99%
“…and demonstrated for their capability of realizing PIT as an analogy to EIT in the atomic system. [104][105][106][107][108][109][110][111][112][113][114][115] In 2008, Zhang et al demonstrated a novel plasmonic metamaterial structure consisting of a radiative element and a dark element that enables PIT to appear. [116] Figure 7a shows the alignment of this plasmonic structure, and it is advantageous in room-temperature operation, wide bandwidth, and easy integration with plasmonic circuit.…”
Section: Plasmon-induced Transparencymentioning
confidence: 99%